Bank Closure Policies and Capital Requirements: a Note - Elettra Agliardi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
A bank closure policy problem is analysed in a mathematical model within a Black-Scholes framework where an appropriate notion of capital adequacy is introduced. The value of the deposit insurance liabilities and bank equity are derived. The effects of capital requirements on risk-shifting and bank reorganization are discussed, with a comparison of the impact of the Basel I and II Accords on banks' behaviour.
Keywords: 330